The Effects of Turmeric Extract (Curcuma domestica Val) on Cigarette Smoke Cardiotoxicity in The Wistar Rats - Nida Ul Millah; Agapietta Kusumawardani; Laelatul Rahmad; Novi Herliyani; Kurniati Sarwendah; Bambang Sutrisno; Hastari Wuryastuty; R Wasito (Jurnal Sain Veteriner, 2013)
Abstract            The objective of this research is to determine the effects of turmeric (Curcuma domestica Val) extract administration toward heart histopathologic lesions of male albino Wistar rats + 3 months old exposed by cigarette smoke. Twenty male Wistar rats were divided randomly into four groups of five each: Group I was given neither cigarette smoke exposure nor turmeric extract administration (control) (KI), Group II was given cigarette smoke exposure of 9 cigarettes/ day (KII), Group III was given 1 ml turmeric extract 0.25% (KIII) and Group IV was given cigarette smoke exposure of 9 cigarettes/ day and 1 ml turmeric extract 0.25% (KIV). After 2 months of treatment, necropsy was conducted to all rats and the heart samples were collected to be processed histopatologically and stained routinely with hematoxylin-eosin. The results of the present study indicated that the cigarette smoke caused cardiomyopathy in KII marked by the histopathologic lesions such as vacuolation, homogeneous eosinophilic cytoplasms, edema and necrosis of myocardia, also congestion and mild hemorrhages (KII). Whereas, rats in Groups KI, KIII and KIV had normal histologic structures of myocardia. It is concluded, that turmeric extract could be a preventive herbs toward cardiotoxic effects of cigarette smoke. Further research has to be conducted to determine the anti cardiomyopathy mechanism of turmeric rhizome due to cigarette smoke exposure.